Respuesta :
-77
You first solve for s(x) by plugging in 5 as the variable
-3*5-4=-19
You then plug the -19 into t(x) and 4*-19-1= -77
You first solve for s(x) by plugging in 5 as the variable
-3*5-4=-19
You then plug the -19 into t(x) and 4*-19-1= -77
Hello!
The answer is:
[tex]t(s(5))=-77[/tex]
Why?
To solve the problem, first, we need to compose the functions, and then evaluate the obtained function. Composing function means evaluating a function into another function.
We have that:
[tex]f(g(x))=f(x)\circ g(x)[/tex]
From the statement we know the functions:
[tex]s(x)=-3x-4\\t(x)=4x-1[/tex]
We need to evaluate the function "s" into the function "t", so:
[tex]t(s(x))=4(-3x-4)-1\\\\t(s(x))=-12x-16-1=-12x-17[/tex]
Now, evaluating the function, we have:
[tex]t(s(5))=-12(5)-17=-60-17=-77[/tex]
Have a nice day!